System Usability Scale Formula as Alternative for Calculating Composite Score of Likert-type Items - Stephen, Donald; Shahren, Ahmad Zaidi Adruce; Ng, Giap Weng (2015)
Since its conception, Likert Scales have been used extensively in various fields. There are many ways to describe data obtained with Likert scales. In Human Factors research, System Usability Scale (SUS) is a widely adapted Likert Scale instrument to assess the usability of various products and systems. Researchers often have the tendency to modify SUS to fit their context of use, leading to various versions of SUS. Calculation of the composite score for SUS instrument does not involve computation of arithmetic mean/sum and re-coding of statements. SUS formula obtains the score for each Likert-type items and convert them into a single scale range from 0 to 100. Although SUS is a popular instrument, there is no formula introduced to facilitate the calculation of scale. This article aims to introduce a formula to facilitate the calculation of various versions of SUS with different number of items, number of positive and negative statements, as well as scale size. Although primarily meant for SUS practitioners, the formula presented can be used for any instrument adapting Likert-type items should the researchers decide to transform responses into 0-100 scale instead of computation of mean or sum for various statistical analyses. The controversial computation of mean for Likert Scales has been subjected to decades of debate. This article demonstrates an alternate method to calculate composite score of Likert-type items based on calculation of SUS. Results show the formula yield the same results and perfect relationship with mean and sum for various tests, indicating it can be used as an alternative to mean and sum as a composite score of Likert-types items.